Exchange Rate Volatility and World Trade. (Occasional Papers; Occasional Paper, 1984)
In View of the continuation of substantial movements in exchange rate relationships among major currencies, the recent increase in protectionist pressures, and the disappointing performance of world trade, renewed concern has been expressed about the possible adverse effects of exchange rate variability on trade. Against the background of this concern, the following decision was reached at the ministerial meeting of the General Agreement of Tariffs and Trade (GATT) in November 1982.